EDUKASI PENERAPAN CASH FLOW PADA USAHA MIKRO DI WISATA BALE TANI - Wicaksono, Agung Prasetyo Nugroho; Soelistyo, Aris; Riyanto, Wahyu Hidayat (Jurnal Pengabdian Masyarakat dan Lingkungan, 2023)
The purpose of this service agenda is to assist partners in implementing transparency in the use of business operational funds. The partner's problem is the inability to manage business operational funds which become one with the partner's personal funds. The solution provided is computerized cash flow training so that partners are more transparent in the use of operational funds. Our partners are residents of Banjaragung Village, Jombang Regency who have micro-businesses selling food and drinks at the Bale Tani Tourism location, Jombang Regency. The service method is to carry out a simulation of excel-based cash flow reports to partners along with discussions so that partners are able to implement the technology provided. The result of this dedication is that partners implement continuous cash flow reports as a media for transparency in the use of their operational funds.